High-performance oriented composite resin as well as preparation method and application thereof
By combining photocuring 3D printing and electric field dielophoresis technology, nanofillers can form efficient thermal conduction channels under the action of electric fields, solving the problem of insufficient thermal conductivity in the prior art, and achieving high-performance composite resin electrical insulation materials.
Patent Information
- Application Number
- CN202411952236.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-22
AI Technical Summary
The existing photocuring 3D printing technology cannot achieve the orientation arrangement of nano-scale fillers in layer thickness accuracy, resulting in insufficient thermal conductivity and difficulty in meeting the insulation and safety requirements of high-voltage equipment.
By combining photocuring 3D printing with electric field dielophoresis technology, the nanofillers are connected head-tail and overlapped into bridges in a direction parallel to the electric field, thereby forming an efficient thermal conduction channel.
It significantly improves the thermal conductivity of composite resin, makes up for the disadvantage that photocuring 3D printing cannot achieve nanofiller orientation arrangement, and improves the performance of electrical insulating materials.
Smart Images

Figure CN119859369A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating non-metallic materials, and specifically relates to a high-performance oriented composite resin and a preparation method and application thereof. Background Art
[0002] After cross-linking and curing, epoxy resin has good mechanical strength, insulation performance, aging resistance and other characteristics, and is widely used in power system equipment, power electronic packaging and other fields. However, epoxy resin has poor thermal conductivity. At the same time, with the rapid development of modern power equipment, the voltage level will continue to increase, and the insulation and safety of epoxy resin will face greater challenges.
[0003] At present, the methods for improving the thermal conductivity of epoxy resin composite insulation materials at home and abroad are mainly divided into two types: filling type and intrinsic type. The intrinsic thermal conductivity type is to improve the thermal conductivity by increasing the crystallinity of the polymer or the orderliness of the molecular chain segment arrangement during the material synthesis process, reducing phonon scattering to increase the phonon free path and increase the transmission speed of phonons in the polymer, but its preparation is difficult and costly, and the thermal conductivity of epoxy resin is mainly enhanced by filling type. Filling type enhanced thermal conductivity refers to filling particles with higher thermal conductivity in the polymer matrix to improve thermal conductivity, but achieving high thermal conductivity requires thermal conductive particles to contact each other to form a path, and heat is transferred along the thermal conductive path formed by the thermal conductive particles. To achieve a thermal conductive path, the content of thermal conductive fillers will be higher. A higher filler content will result in a lower content of epoxy matrix, which greatly increases the difficulty of the molding process and reduces the mechanical properties and insulation properties of epoxy resin composites.
[0004] Achieving high thermal conductivity with less filler content can be achieved through layer-by-layer curing molding using photocuring 3D printing technology. By controlling the printing accuracy, the filler is squeezed during the layer-by-layer printing process to form an effective arrangement between layers, achieving interlayer orientation. At the same time, the photocuring 3D printing process is convenient, fast and highly accurate during the preparation process. However, photocuring 3D printing can only achieve orientation for two-dimensional fillers with a micron-level accuracy and cannot achieve orientation arrangement for nanofillers. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-performance oriented composite resin.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0009] An acrylate resin and a photosensitive diluent are mixed to obtain a mixture I, and a photoinitiator and a vinyl ester resin are added to the mixture I to obtain a photosensitive resin matrix;
[0010] Adding boron nitride nanosheets to a photosensitive resin matrix, mixing and stirring evenly in a vacuum degassing device to obtain a 3D printing resin matrix mixture;
[0011] The 3D printing resin matrix mixture is poured into the 3D printer material tank, a copper electrode is placed, and 3D printing is performed under DC electric field conditions to obtain a high-performance oriented composite resin.
[0012] As a preferred embodiment of the method for preparing the high-performance oriented composite resin of the present invention, the acrylic resin includes one or more of tripropylene glycol diacrylate (TPGDA), trimethylolpropane triacrylate (TMPTA), and glycidyl methacrylate (GMA).
[0013] As a preferred embodiment of the method for preparing the high-performance oriented composite resin of the present invention, the photosensitive diluent includes one or more of isooctyl acrylate (EHA), (meth)hydroxy acrylate (HEA, HEMA, HPA), neopentyl glycol diacrylate (NPGDA), and glycidyl methacrylate (GMA), and the amount used is 30wt% to 35wt% of the mixture I.
[0014] As a preferred embodiment of the method for preparing the high-performance oriented composite resin of the present invention, the photoinitiator includes one or more of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide (TPO), (2,4,6-trimethylbenzoyl phosphonic acid ethyl ester) (TPO-L), phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (819 photoinitiator), and benzophenone initiator (PBZ), and the amount used is 0.5wt% to 1wt% of the mixture I.
[0015] As a preferred solution of the method for preparing the high-performance oriented composite resin of the present invention, the vinyl ester resin includes epoxy acrylate resin, and the amount used is 5-10wt% of the mixture I.
[0016] As a preferred solution of the method for preparing the high-performance oriented composite resin of the present invention, the amount of the boron nitride nanosheets used is 10-20wt% of the photosensitive resin matrix.
[0017] As a preferred solution of the method for preparing the high-performance oriented composite resin of the present invention, in the 3D printing, the bottom layer exposure time is 33 to 40 seconds and the normal exposure time is 10 to 15 seconds.
[0018] As a preferred solution of the method for preparing the high-performance oriented composite resin of the present invention, the electric field strength of the DC electric field set for 3D printing is 0 kV / cm to 1 kV / cm.
[0019] Another object of the present invention is to provide a high-performance oriented composite resin.
[0020] Another object of the present invention is to provide a high-performance oriented composite resin for use as a high thermal conductivity electrical insulation material.
[0021] Beneficial effects of the present invention:
[0022] In view of the defects of the existing photocuring 3D technology that the layer thickness accuracy cannot be achieved at the nano level and the fillers cannot be squeezed to form an effective arrangement between layers in the layer-by-layer printing process like micron-level fillers, the present invention proposes a method for preparing a high-performance oriented composite resin, which combines photocuring 3D printing with the dielectrophoresis effect of an electric field on nanofillers to prepare a high-performance composite resin electrical insulating material, and selectively utilizes the electric field to subject the nanofillers to the effects of electrophoresis and dielectrophoresis, so that the fillers are connected head to tail and bridged in a direction parallel to the electric field, providing a path for heat conduction, thereby making up for the disadvantage that photocuring 3D printing cannot achieve oriented arrangement of nanofillers. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 This is a flow chart for preparing the high-performance oriented composite resin in Example 1 of the present invention.
[0025] Figure 2 This is a cross-sectional morphology diagram of the high-performance oriented composite resin prepared in Example 1 of the present invention.
[0026] Figure 3 These are the photocuring printing effect diagrams under different schemes of Example 6 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] Unless otherwise specified, all the drugs used in the present invention are commercially available in the art. The list of related drugs is shown in Table 1, and the list of equipment is shown in Table 2.
[0031] Material Name purity abbreviation Photosensitive diluent (GMA) Industrial pure 99% GMA Boron Nitride Nanosheets 200-300nm BNNS Tripropylene glycol diacrylate Industrial pure 99% TPGDA Trimethylolpropane triacrylate Industrial pure 99% TMPTA Epoxy Acrylate Industrial pure 99% EA Photoinitiator 819 Light yellow powder BAPO
[0032] Table 2
[0033] Device Name model Vacuum degassing machine DAC1200-300 3D Printer LD-002H DC Power Supply / Copper electrode /
[0034] The product test of the present invention refers to the following method:
[0035] Cross-sectional morphology: The cross-sectional morphology of the oriented boron nitride nanosheet composite resin was observed using a Sirion 200 scanning electron microscope to observe the concentration distribution of the boron nitride nanosheets at different magnifications and their dispersion, arrangement direction and orientation degree in the composite resin.
[0036] Thermal conductivity test: The prepared high-performance oriented composite resin sample was polished into a square piece with a side length of 10 mm and a thickness of 1 mm. The thermal diffusion coefficient (α) of the sample along the thickness direction was tested using an LFA467 laser thermal conductivity instrument. The test temperature was room temperature 25°C. A layer of black graphite oil was sprayed on the surface of the sample so that it could absorb most of the laser pulse energy.
[0037] The thermal conductivity λ of the sample is calculated by the formula λ=α / (ρ×Cp);
[0038] Where Cp is the constant pressure specific heat capacity of the sample measured by comparing with the reference sample, and ρ is the density of the sample measured by measuring the actual volume and weight of the sample.
[0039] Dielectric spectrum test: The relative dielectric constant, dielectric loss factor and volume conductivity of the prepared high-performance oriented composite resin sample at room temperature were tested using a Concept 40 broadband dielectric impedance spectrometer. The test frequency was 10 -2 ~10 6 Hz, the test AC voltage is 1V, the sample is disc-shaped, with a diameter of 12mm and a thickness of 1mm.
[0040] Example 1
[0041] Reference Figure 1 This embodiment provides a method for preparing a high-performance oriented composite resin:
[0042] 1) Under light-proof conditions, firstly, a mixture I is prepared according to a ratio of tripropylene glycol diacrylate (TPGDA): photosensitive diluent (GMA): trimethylolpropane triacrylate (TMPTA) = 6:3:1, that is, the amount of the photosensitive diluent in the mixture I is 30wt%, and 0.5wt% of photoinitiator 819 and 5wt% of epoxy acrylate (EA) are added thereto compared to the mass of the mixture I, to obtain a photosensitive resin matrix;
[0043] 2) adding 20 wt% of boron nitride nanosheets to the photosensitive resin matrix, mixing and stirring evenly in a vacuum degassing device under a vacuum degree of 0.5 kPa to obtain a 3D printing resin matrix mixture;
[0044] 3) Pour the 3D printing mixture into the trough of the 3D printer, place the copper electrodes connected with wires in the appropriate position in the trough (on both sides of the printing platform), so that the electric field generated covers the 3D printing resin matrix mixture while maintaining a suitable distance from the trough wall, select the model to be printed, adjust the bottom exposure time to 40s, the normal exposure time to 15s, and adjust the DC power supply voltage to make the DC electric field strength 0.5kV / cm. Under this electric field condition, perform layer-by-layer 3D printing, and the thickness of each layer is 200nm to obtain the high-performance oriented composite resin of this embodiment.
[0045] The cross-sectional morphology of the high-performance oriented composite resin prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that under the action of electrophoresis, the fillers are aggregated and arranged in sequence along the direction of the electric field, and the fillers are connected end to end to form an obvious heat conduction channel.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that the magnitude of the DC electric field applied in step 3) is adjusted to 0.3 kV / cm, and the remaining steps and processes are all based on embodiment 1 to obtain the high-performance oriented composite resin of this embodiment.
[0048] Example 3
[0049] The difference between this embodiment and embodiment 1 is that the magnitude of the DC electric field applied in step 3) is adjusted to 0.1 kV / cm, and the remaining steps and processes are all based on embodiment 1 to obtain the high-performance oriented composite resin of this embodiment.
[0050] Example 4
[0051] The difference between this embodiment and embodiment 1 is that the magnitude of the DC electric field applied in step 3) is adjusted to 0.6 kV / cm, and the remaining steps and processes are all based on embodiment 1 to obtain the high-performance oriented composite resin of this embodiment.
[0052] Example 5
[0053] The difference between this embodiment and embodiment 1 is that the magnitude of the DC electric field applied in step 3) is adjusted to 0.9 V / cm, and the remaining steps and processes are all based on embodiment 1 to obtain the high-performance oriented composite resin of this embodiment.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that no electric field strength is applied in step 3), and the remaining steps and processes are all referred to Example 1 to obtain the high-performance oriented composite resin of this comparative example.
[0056] Comparative Example 2 Pure resin matrix
[0057] The difference between this comparative example and Example 1 is that in the adjustment step 2), the direct current not applied in the adjustment step 3) is not applied to the photosensitive resin matrix, and the remaining steps and processes are all referred to Example 1 to obtain the high-performance oriented composite resin of this comparative example.
[0058] The thermal conductivity of the high-performance oriented composite resins prepared in Examples 1 to 5 and Comparative Examples 1 and 2 was tested, and the results are shown in Table 3.
[0059] Table 3
[0060]
[0061] It can be seen from Table 3 that the thermal conductivity of the composite resin can be significantly improved by applying an electric field during the printing process. This is because in the present invention, under the action of the electric field, the nanofillers can be affected by electrophoresis and dielectrophoresis, so that they are connected head to tail and bridged in a direction parallel to the electric field, providing a path for heat conduction, thereby compensating for the disadvantage that light-curing 3D printing cannot achieve the orientation arrangement of nanofillers.
[0062] However, the boron nitride nanoparticles (BNNS) are oriented and arranged in the resin matrix with the maximum field strength. When the applied electric field strength exceeds the maximum field strength, the BNNS will undergo electrophoresis in the medium and the particles will gather at the positive electrode or negative electrode. The higher the electric field strength, the more obvious the electrophoresis phenomenon of the BNNS particles will be. During the printing process, the BNNS particles will gather faster and more at the positive electrode or negative electrode, which will lead to performance degradation.
[0063] Example 6
[0064] This embodiment is used to explore the influence of the composite types of mixture I on the technical effect. The difference from Example 1 is that the mixture I is adjusted to #1TPGDA, #2TMPTA, #3TPGDA:GMA=6:3, #4TPGDA:TMPTA=6:1, and #5GMA:TMPTA=6:1, respectively. The remaining steps and processes are all referred to Example 1. Resins of different types of mixtures I are prepared, and the relevant properties are measured and compared with TPGDA:GMA:TMPTA=6:1:3 in Example 1. The results are shown in Table 5.
[0065] Table 5
[0066]
[0067] It can be seen from Table 5 that by changing the type of mixture I, the thermal conductivity of the composite resin is not affected much without affecting the integrity of the printed sample (No. #3, #4, #6). However, changing the type of mixture I will lead to poor printing results, such as overexposure, underexposure or non-forming. Figure 3 As shown, there are theoretical renderings of photocuring printing and actual printing renderings numbered #1, #2, and #5. Therefore, in order to ensure model forming and accuracy, the resin matrix combination method prepared in this patent has important reference significance.
[0068] Example 7
[0069] This embodiment is used to explore the influence of the composite ratio of mixture I on the technical effect. The difference from Example 1 is that the ratio of the mixture of epoxy acrylate resin TPGDA, TMPTA and photosensitive diluent GMA in step 1) is adjusted to the following four ratios and numbered: #1 TPGDA:GMA:TMPTA=6.5:2.5:1, #2 TPGDA:GMA:TMPTA=7:2:1, #3 TPGDA:GMA:TMPTA=6:2.5:1.5, #4 TPGDA:GMA:TMPTA=6:2:2, #5 TPGDA:GMA:TMPTA=6.4:3:0.6, #6 TPGDA:GMA:TMPTA=6.7:3:0.3, #7 TPGDA:GMA:TMPTA=5.7:3:1.3, #8 TPGDA:GMA:TMPTA=5.3:3:1.7 The remaining steps and processes are all referred to Example 1 to obtain the high-performance oriented composite resin of this embodiment.
[0070] The relevant properties were measured and compared with 6:3:1 in Example 1. The results are shown in Table 6.
[0071] Table 6
[0072]
[0073]
[0074] It can be seen from Table 6 that appropriately changing the compounding ratio of mixture I has little effect on the thermal conductivity of the composite resin without affecting the integrity of the printed sample. However, the compounding ratio of mixture I should not be changed too much. For example, when the amount of TMPTA in the epoxy acrylate resin is too much, the curing speed will be too fast, the mechanical properties of the printed model will drop sharply, and it will also make demolding difficult. Too little TMPTA will also increase the printing curing time, and it is difficult to ensure the molding accuracy.
[0075] The main component of photosensitive resin is monomer, commonly used are acrylate, epoxy, aromatic, vinyl, etc. In this experiment, the most commonly used acrylate for photocuring 3D printing is selected as the photosensitive resin matrix. In order to ensure the printing speed and accuracy of the photosensitive resin during the photocuring process, as well as the performance of the photosensitive resin material after curing, a variety of monomers are selected for use. Tripropylene glycol diacrylate (TPGDA), trimethylolpropane triacrylate (TMPTA), and glycidyl methacrylate (GMA) are selected and mixed in a ratio of TPGDA: GMA: TMPTA = 6:3:1. TPGDA has two carbon-carbon double bonds that help to quickly polymerize and cure under UV irradiation. GMA is a monomer with both double bonds and epoxy groups. As a photosensitive diluent, one of its double bonds can form a functional copolymer with the other two acrylates. The epoxy group can toughen the polymer. TMPTA is a typical trifunctional monomer with three carbon-carbon double bonds. Adding it can further increase the curing speed and have a high cross-linking density to improve printing accuracy.
[0076] Epoxy acrylate resin (EA) is a vinyl ester resin with extremely high viscosity and is not suitable for use alone. Adding 5 to 10 wt% to resin I will have little effect on the overall viscosity, while helping to enhance the hardness, glossiness, corrosion resistance, heat resistance and electrochemical properties of the composite resin.
[0077] Example 8
[0078] This embodiment is used to explore the effect of the amount of boron nitride nanosheets on the technical effect. The difference from Example 1 is that the content of boron nitride nanosheets in step 2) is adjusted to have the following four proportions and are numbered: #1hBN accounts for 0wt%, #2hBN accounts for 10wt%, #3hBN accounts for 15wt%, and the remaining steps and processes are all referred to Example 1 to obtain the high-performance oriented composite resin of this embodiment.
[0079] The relevant properties were measured and compared with those in Example 1. The results are shown in Table 7.
[0080] Table 7
[0081]
[0082] Example 9
[0083] This embodiment is used to explore the influence of the type of nanofiller on the technical effect. The difference from Embodiment 1 is that the type of filler in step 2) is adjusted and the applied content of each filler is kept unchanged. In order not to change the insulating properties of the composite resin, inorganic ceramic fillers are selected for addition. Four commonly used inorganic ceramic fillers are selected, namely alumina (Al2O3), aluminum nitride (AlN), and silicon nitride (Si4N3). Different types of filler resins are numbered: #1Al2O3, #2AlN, and #3Si4N3. The remaining steps and processes are all referred to Embodiment 1 to obtain the high-performance oriented composite resin of this embodiment.
[0084] The relevant properties were measured and compared with those in Example 1. The results are shown in Table 8.
[0085] Table 8
[0086]
[0087] As can be seen from Table 8, changing the type and amount of nanofillers has a great influence on the thermal conductivity of the composite resin. Boron nitride nanosheets have the highest thermal conductivity due to their excellent intrinsic thermal conductivity. Fillers with lower intrinsic thermal conductivity often need to have an effect on the thermal conductivity of the composite resin when the filling amount is high, and basically have no effect when the filling amount is low. The use of dielectrophoresis technology to induce the orientation of nanofillers often has a better effect when the matrix viscosity is low and the filler content is low. Selecting boron nitride nanosheets with high intrinsic thermal conductivity is an important step in the feasibility of this embodiment.
[0088] In summary, the present invention aims at the defects of the existing photocuring 3D technology that the layer thickness accuracy cannot be achieved at the nano level and the fillers can no longer be squeezed in the layer-by-layer printing process like micron-level fillers to form an effective arrangement between layers. A method for preparing a high-performance oriented composite resin is proposed. The photocuring 3D printing is combined with the dielectrophoresis effect of the electric field on the nanofillers to prepare a high-performance composite resin electrical insulating material. The electric field is used to subject the nanofillers to the effects of electrophoresis and dielectrophoresis, so that the fillers are connected head to tail and bridged in a direction parallel to the electric field, providing a path for heat conduction, which can make up for the disadvantage that photocuring 3D printing cannot achieve oriented arrangement of nanofillers.
[0089] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a high-performance oriented composite resin, characterized in that: include, An acrylate resin and a photosensitive diluent are mixed to obtain a mixture I, and a photoinitiator and a vinyl ester resin are added to the mixture I to obtain a photosensitive resin matrix; Adding boron nitride nanosheets to a photosensitive resin matrix, mixing and stirring evenly in a vacuum degassing device to obtain a 3D printing resin matrix mixture; The 3D printing resin matrix mixture is poured into the 3D printer material tank, a copper electrode is placed, and 3D printing is performed under DC electric field conditions to obtain a high-performance oriented composite resin.
2. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: The acrylic resin includes one or more of tripropylene glycol diacrylate, trimethylolpropane triacrylate, and glycidyl methacrylate.
3. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: The photosensitive diluent includes one or more of isooctyl acrylate, hydroxy (meth)acrylate, neopentyl glycol diacrylate, and glycidyl methacrylate, and the amount used is 30 wt % to 35 wt % of the mixture I.
4. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: The photoinitiator includes one or more of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, (2,4,6-trimethylbenzoyl phosphonic acid ethyl ester), phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, and benzophenone initiators, and the amount used is 0.5wt% to 1wt% of the mixture I.
5. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: The vinyl ester resin includes epoxy acrylate resin, and the amount used is 5-10wt% of the mixture I.
6. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: The amount of the boron nitride nanosheets used is 10-20 wt % of the photosensitive resin matrix.
7. The method for preparing a high-performance oriented composite resin according to claim 1, characterized in that: In the 3D printing, the bottom layer exposure time is 33 to 40 seconds and the normal exposure time is 10 to 15 seconds.
8. The method for preparing a high-performance oriented composite resin according to claim 7, characterized in that: The electric field strength of the DC electric field set for the 3D printing is 0 kV / cm to 1 kV / cm.
9. A high-performance oriented composite resin prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high-performance oriented composite resin according to claim 9 as a high thermal conductivity electrical insulation material.